To find the distance between the points \((-1, 6)\) and \((5, -2)\), we can use the distance formula, which is derived from the Pythagorean Theorem:
\[ d = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} \]
In this case, let \( (x_1, y_1) = (-1, 6) \) and \( (x_2, y_2) = (5, -2) \).
Now, substitute the coordinates into the formula:
\[ d = \sqrt{(5 - (-1))^2 + (-2 - 6)^2} \]
Calculating the differences:
\[ d = \sqrt{(5 + 1)^2 + (-2 - 6)^2} \] \[ d = \sqrt{(6)^2 + (-8)^2} \]
Now calculate the squares:
\[ d = \sqrt{36 + 64} \] \[ d = \sqrt{100} \] \[ d = 10 \]
The length between the points \((-1, 6)\) and \((5, -2)\) is \(10\).
So the correct response is:
10